2021
DOI: 10.1136/bmjspcare-2021-003173
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality in hospice: improved patient well-being

Abstract: BackgroundVirtual reality (VR) technology as a therapeutic intervention has been gaining attention in healthcare settings in recent years. Studies suggest that using the technology can help alleviate symptoms such as pain and anxiety and induce positive emotions for people in hospital. Managing symptoms and promoting emotional and psychological well-being are core palliative care goals of relieving suffering of people with life-limiting illness. Accordingly, VR may be highly beneficial for use in hospice care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…Qualitative data from 14 participants in Brungardt et al [ 34 ] reported the VR intervention as comfortable and easy to engage with; however, two participants found the experience acceptable but did not enjoy it. Similarly, Lloyd and Haraldsdottir [ 32 ] found that most participants described their experience with the VR intervention positively, including reports of joy and happiness and “being lifted out of their current situation” (p348). In addition, some neutral responses and very little negative feedback were provided.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Qualitative data from 14 participants in Brungardt et al [ 34 ] reported the VR intervention as comfortable and easy to engage with; however, two participants found the experience acceptable but did not enjoy it. Similarly, Lloyd and Haraldsdottir [ 32 ] found that most participants described their experience with the VR intervention positively, including reports of joy and happiness and “being lifted out of their current situation” (p348). In addition, some neutral responses and very little negative feedback were provided.…”
Section: Resultsmentioning
confidence: 96%
“…No overall statistical differences were found; however, it was reported that those in the personalised group appeared to experience the greatest improvement in tiredness, anxiety, and psychological well-being, while those in the non-personalised group appeared to experience the greatest improvements in tiredness and drowsiness using mean difference scores. Other studies qualitatively reported an improvement in psychological [ 22 , 32 , 33 , 34 ] and somatic outcomes [ 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations